Effects of environment, nitrogen, and sulfur on total phenolic content and phenolic acid composition of winter wheat grain. Issue 4 (8th April 2021) - Tian, Wenfei; Wilson, Tara L.; Chen, Gengjun; Guttieri, Mary J.; Nelson, Nathan O.; Fritz, Allan; Smith, Gordon; Li, Yonghui
Abstract: Background and objectives: Health benefits of whole wheat are partially attributed to phenolic compounds. This study reports the effects of harvest year (Y), nitrogen (N) and sulfur (S) fertilization, and wheat variety (V) on total phenolic content (TPC) and phenolic acid composition of wheat grains. Findings: The year effect was significant for TPC and all phenolic acids except for syringic acid. The TPC and phenolic acid composition significantly differed among the varieties, except for vanillic acid concentration. Increased nitrogen fertilizer led to increased production of trans ‐ferulic acid, and sulfur application affected the response to nitrogen fertilizer application. Varieties also differed in the response of phenolic acid concentration and composition to sulfur application. Conclusions: Year, sulfur fertilization, and wheat variety significantly influenced the total phenolic content and phenolic acid composition of wheat grains. Though nitrogen and sulfur applications had significant effect on wheat phytochemicals, environment (e.g., year), and variety, differences dominated the analysis of variance. Significance and novelty: To our knowledge, this is the first study that reports the effects of nitrogen, sulfur, variety, harvest year, and their interactions on phenolic profiles of hard red winter wheat grains. These results will benefit future wheat production practices that aim to produce wheat grains enriched with natural antioxidants.